Corrosion characterization of the experimental alloy Ti-35Nb-7Zr-5Ta by electrochemical techniques (Research, Society and Development, 2021)
The objective of the present study was to evaluate the corrosion resistance of the experimental alloy Ti-35Nb-7Zr-5Ta, modified by laser beam, in a physiological solution of 0.9% NaCl. This evaluation was carried out by open circuit potential analysis (EOCP), potentiodynamic polarization curves and cyclic polarization curves. The open circuit potential curves show the specimen irradiated by laser beam at 35 Hz presented a more stable and corrosion resistant surface. It was observed in the polarization curves, low current densities in the order of nA /cm2, for all specimen indicating an expected passive behavior for the investigated alloy. The cyclic polarization curves show that for specimen treated with laser, the potential for repassivation (Er) is greater in relation to the potential for corrosion (Ecorr), which indicates greater resistance to corrosion of metal alloys when treated with laser.